Payments and Central Bank Policy - Søren Korsgaard (Copenhagen Business School (CBS), 2016)
This thesis consists of three chapters. The rst, "Paying for Payments", examines the role of interchange fees in payment card networks. The second, "Bank Liquidity and the Interbank Market" (co-authored with Mikael Reimer Jensen), investigates how banks' liquidity holdings at the central bank a ect outcomes in the money market. The third, "Collateralized Lending and Central Bank Collateral Policy", considers the emergence of credit constraints under collateralized lending, and how central banks use collateral policy to mitigate these constraints. While the chapters can be read independently, they share common themes. Each chapter is concerned with payments in one way or another, each is concerned with the e ciency of market outcomes, and, to the extent that there is scope for improving these outcomes, each discusses the appropriate role for policy, in particular central bank policy.
hdl:10398/9313
Keywords: 650